The Role of Challenges in Mediating Boredom's Influence on Career Aspirations - Ni Komang Diah Permata Sari; I Gusti Made Suwandana (Jurnal sosial dan sains, 2024)
Background: Career aspirations play a key role in guiding individuals toward their future goals. These career aspirations become an important part of a student's journey during their studies and will develop over time. Purpose: The purpose of this study was to determine the role of challenges in mediating the influence of boredom on career aspirations Method: The research method used is the simple random sampling method. Interviews and the distribution of questionnaires carried out data collection. The data analysis technique used in this study is path analysis with SPSS Results: The results of this study show that boredom and challenges have a significant negative effect on career aspirations, boredom has a significant positive effect on challenges, and challenges mediate the influence of boredom on career aspirations. The implications of this study theoretically support the findings of previous research results Conclusion: The practical implications of the Management Study Program, Faculty of Economics and Business, Udayana University are to increase students' career aspirations by paying attention to the challenges and boredom felt by students